Association between motor timing and treatment outcomes in patients with alcohol and/or cocaine addiction in a rehabilitation programme - Young, Susanne Yvette (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017.